2011
DOI: 10.1371/journal.pone.0024130
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Epidemiological History of HIV-1 CRF14_BG

Abstract: BackgroundCRF14_BG isolates, originally found in Spain, are characterized by CXCR4 tropism and rapid disease progression. This study aimed to identify the origin of CRF14_BG and reconstruct its epidemiological history based on new isolates from Portugal.Methodology/Principal FindingsC2V3C3 env gene sequences were obtained from 62 samples collected in 1993–1998 from Portuguese HIV-1 patients. Full-length genomic sequences were obtained from three patients. Viral subtypes, diversity, divergence rate and positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…The origin of CRF14_BG and CRF35_AD was previously estimated in Portugal (Bartolo et al, 2011) and respectively in Afghanistan/ Iran (Sanders-Buell et al, 2007). Subtypes A and B studied clusters originated/have their origin in Greece (Paraskevis et al, 2013).…”
Section: Number Of Lineagesmentioning
confidence: 85%
“…The origin of CRF14_BG and CRF35_AD was previously estimated in Portugal (Bartolo et al, 2011) and respectively in Afghanistan/ Iran (Sanders-Buell et al, 2007). Subtypes A and B studied clusters originated/have their origin in Greece (Paraskevis et al, 2013).…”
Section: Number Of Lineagesmentioning
confidence: 85%
“…This observation is consistent with previous studies that showed, using both genotypic and phenotypic testing, that the CXCR4 phenotype was very common at baseline among CRF14_BG-infected patients. 29 This leads to more rapid disease progression in patients infected with CRF14_BG. 30 Among newly diagnosed patients infected heterosexually, the late presenters (CD4 counts < 250 and/or CDC stage C) carrying F1 subtype strains were frequent.…”
Section: Discussionmentioning
confidence: 99%
“…36 Although it had been initially isolated in the early 2000s in Spanish IDUs from Galicia, near the border with Portugal, recent phylodynamic analysis of CRF14_BG indicated a Portuguese origin; in Portugal, subtypes B and G are cocirculating. 29 In Romania, it was identified almost exclusively in drug-injecting patients, the same risk category as in the origin countries, Spain and Portugal. Estonia, Italy, and Germany also reported HIV cases with CRF14 strains, but fewer accounts of this particular CRF were recorded in recent years in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Subtype G and other non-B subtypes were introduced in Portugal following intense migration between Portugal and its former African colonies in the late 1970s and early 1980s, especially because of the Portuguese Colonial War that involved multiple theatres of operation including Angola with a high degree of HIV-1 group M genetic diversity (Bártolo et al, 2009; Carvalho et al, 2015; Vermund and Leigh-Brown, 2012). Subtype G, which also circulates among PWID in Spain (Delgado et al, 2002; Pérez-Alvarez et al, 2003), recombined with subtype B, probably in Portugal early in the history of the epidemic, creating CRF14_BG that has been detected in Portugal, at low prevalence in the region of Galicia, Spain, and in some other European settings (Bártolo et al, 2011; Carvalho et al, 2015; Duque et al, 2003; Harris et al, 2005; Thomson et al, 2001). Although CRF14_BG soon became the predominant CRF in Portugal and Spain, its prevalence has been decreasing, a finding that might be associated with its high pathogenicity or its tendency to recombine with other strains, but also to the declining prevalence of HIV-1 among PWID (Bártolo et al, 2011; Carvalho et al, 2015).…”
Section: Molecular Epidemiology Of Hiv Among Pwid In Western and Cmentioning
confidence: 99%